2020
DOI: 10.3389/fmed.2020.00445
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Prediction of Hospital Mortality in Patients With Postoperative Sepsis

Abstract: Introduction: The incidence of postoperative sepsis is continually increased, while few studies have specifically focused on the risk factors and clinical outcomes associated with the development of sepsis after surgical procedures. The present study aimed to develop a mathematical model for predicting the in-hospital mortality among patients with postoperative sepsis. Materials and Methods: Surgical patients in Medical Information Mart for Intensive Care (MIMIC-III) database who simultaneously fulfilled Sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…With the development of machine learning algorithms, the magnitude of predictors that can be processed has mainly been largely enriched. Thus, advanced machine learning techniques allow researchers to establish more optimal models in comparison with conventional models ( 16 ). With such models, ICU physicians could be alerted early when patients become complicated and have deteriorated with mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of machine learning algorithms, the magnitude of predictors that can be processed has mainly been largely enriched. Thus, advanced machine learning techniques allow researchers to establish more optimal models in comparison with conventional models ( 16 ). With such models, ICU physicians could be alerted early when patients become complicated and have deteriorated with mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted by Yao et al ( 16 ) explored the death prediction model in postoperative septic patients using the MIMIC-III database. Similar to our results, they also found that the XGBoost model performed better in predicting hospital mortality than the other models.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, sepsis prediction on the ICU is an important and timely problem and an active area of research. Under these circumstances, it is not surprising that some approaches have been developed in parallel to this work [33][34][35][36][37][38][39][40][41][42][43]. It will be an exciting and important avenue for future work to benchmark all these approaches (including ours) against each other and to compare their performances on a unified and realistic set of sepsis labels, for instance, the ones we propose in this work.…”
Section: Parallel Work On Sepsis Predictionmentioning
confidence: 97%
“…For example, Fohner et al used latent Dirichlet Allocation as the un-supervised learning model to assess clinical heterogeneity in sepsis, and Taylor et al applied the random forest model to predict the in-hospital mortality in emergency department patients with sepsis (Taylor et al, 2016;Fohner et al, 2019). Extreme Gradient Boosting (Xgboost), as it functions as an iterative refit of weak classifiers to residuals of previous models (Yao et al, 2020), has become one of the most popular machine learning models, outperforming other models. It has been widely used in different scenarios in medical application Ogunleye and Wang, 2020), and there is no exception for sepsis (Zabihi et al, 2019;Yao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme Gradient Boosting (Xgboost), as it functions as an iterative refit of weak classifiers to residuals of previous models (Yao et al, 2020), has become one of the most popular machine learning models, outperforming other models. It has been widely used in different scenarios in medical application Ogunleye and Wang, 2020), and there is no exception for sepsis (Zabihi et al, 2019;Yao et al, 2020). To our knowledge, there is no analytical tool to predict which COVID-19 patients are most likely to develop sepsis in the near future.…”
Section: Introductionmentioning
confidence: 99%